A Research Review of Muslim Family Law’s & its Contemporary significance - Khan, Shahbaz (Al-Amīr Research Journal for Islamic Studies, 2023)
Islam is a comprehensive system of life that covers all aspects of human life. It is a complete religion given by Allah Ta’ala and it has been created by the unseen being who is fully aware of all the vicissitudes of human life, keeping in mind the strength and weakness of human beings.. As Allah Almighty says in verse 3 of Surat al-Maida: اَلْیَوْمَ اَكْمَلْتُ لَكُمْ دِیْنَكُمْ وَ اَتْمَمْتُ عَلَیْكُمْ نِعْمَتِیْ وَ رَضِیْتُ لَكُمُ الْاِسْلَامَ دِیْنًا On this day I have completed your religion and I have completed my blessing on you and I have accepted the religion of Islam. On this day, I have perfected your religion for you and fulfilled my blessing upon you and I have preferred Islam as your religion for you. From this verse, we are getting a clear proof that Islam is a complete code of life where the system of worship has been given keeping in mind the spirituality and also taking into account the sexual and emotional desires of man. Family laws have also been formulated and provide complete rules and regulations related to it and provide high standards for man to lead a life in the way of purity and purity, which even today’s science is forced to admit. Key Words: Family Laws, Marriage, dowry, Inheritance, Contemporary Significance.